Exploring the association of the discharge medicines review with patient hospital readmissions through national routine data linkage in Wales: a retrospective cohort study. Issue 2 (9th February 2020) - Mantzourani, Efi; Nazar, Hamde; Phibben, Catherine; Pang, Jessica; John, Gareth; Evans, Andrew; Thomas, Helen; Way, Cheryl; Hodson, Karen
Abstract : Objective: To evaluate the association of the discharge medicines review (DMR) community pharmacy service with hospital readmissions through linking National Health Service data sets. Design: Retrospective cohort study. Setting: All hospitals and 703 community pharmacies across Wales. Participants: Inpatients meeting the referral criteria for a community pharmacy DMR. Interventions: Information related to the patient's medication and hospital stay is provided to the community pharmacists on discharge from hospital, who undertake a two-part service involving medicines reconciliation and a medicine use review. To investigate the association of this DMR service with hospital readmission, a data linking process was undertaken across six national databases. Primary outcome: Rate of hospital readmission within 90 days for patients with and without a DMR part 1 started. Secondary outcome: Strength of association of age decile, sex, deprivation decile, diagnostic grouping and DMR type (started or not started) with reduction in readmission within 90 days. Results: 1923 patients were referred for a DMR over a 13-month period (February 2017–April 2018). Provision of DMR was found to be the most significant attributing factor to reducing likelihood of 90-day readmission using χ 2 testing and classification methods. Cox regression survival analysis demonstrated that those receiving the intervention had a lower hospital readmission rate at 40 days (p<0.000, HR: 0.59739, CI 0.5043 to 0.7076). Conclusions: DMR after a hospital discharge is associated with a reduction in risk of hospital readmission within 40 days. Linking data across disparate national data records is feasible but requires a complex processual architecture. There is a significant value for integrated informatics to improve continuity and coherency of care, and also to facilitate service optimisation, evaluation and evidenced-based practice.